PERBANDINGAN KONSUMSI ENERGI LISTRIK TERHADAP BIAYA LISTRIK MENGGUNAKAN SISTEM PRA BAYAR, PASCA BAYAR DAN TENAGA SURYA PADA SKALA RUMAH TANGGA - Kurnia Paranita Kartika Riyanti Kartika (Jurnal Qua Teknika, 2020)
In general, people in Indonesia use the electricity purchasing system from the state electricity company in two ways, namely Postpaid and Prepaid. In postpaid electricity subscription mode, the customer uses electrical energy first and then pays the bill the following month. PLN officers must record the meter, calculate and issue accounts to be paid by customers, bill customers who are late or do not pay, and cut off electricity if consumers are late or do not pay their electricity bills after a certain time. This is a weakness in the postpaid system because of the gradual process before the customer finally makes a bill payment. Prepaid electricity is introduced to customers by providing several conveniences, namely being able to control their own use of electrical energy, customers only need to buy vouchers or tokens according to the desired nominal. This is also a form of sales control carried out by PLN because it can reduce the amount of customer receivables, so there is no need for late fees and can also maintain customer privacy by not calculating kWh meters every month. The solar electric system provides a new breakthrough by utilizing solar energy which is then converted into electrical energy. The use of solar energy for electricity generation has actually been carried out for a long time, namely since the early 1980s, but its application is still limited to small power systems or better known as the Solar Home System (SHS). This research has successfully implemented a comparison of postpaid, prepaid and solar energy use. From the test results, it is found that the most economical prepaid system among other systems applied is the postpaid system and the solar power system. The results of tests carried out at the household scale show that during the 10 years of life, the results of using prepaid electricity are 16.6% more efficient than solar panel systems and 17.7% more efficient than postpaid electricity and prepaid electricity is 1.34% more efficient than postpaid electricity